Maladministration of Official Actions Issuance of Borrow-to-Use Permit for Forest Area - M.Sabaruddin Sinapoy; Basrin Melamba (Journal of Law, Social Science and Management, 2024)
Introduction: Despite having strategically located and sizable woods, Indonesia's management is still subpar. Government officials' poor management of the IPPKH issue has grown to be a major issue. The primary causes include internal problems such a lack of oversight, engagement from third parties, and corruption and collaboration between government officials and other parties. Complicated bureaucracy also makes matters worse. Law enforcement efforts are weakened by a number of important factors, including the lack of public and corporate awareness of the significance of forest sustainability, political influence, the need for state and local revenues, economic pressure, and the interests of particular parties. Government officials are therefore tempted to grant licenses in violation of the law, which results in official maladministration. Objective: This paper seeks to outline the implications of the maladministration of officials in the issuance of the Forest Area Borrowing and Use Permit (IPPKH), as well as the legal position (validity) of the IPPKH due to the maladministration of officials in its issuance. Methods: This type of research employs normative legal research to find legal rules, legal principles, and legal doctrines to answer the legal issues at hand. It also generates new arguments, theories, and conceptions as a prescription in order to address issues. Results The actions of officials who make and issue IPPKH that are not in accordance with statutory regulations can be said to be maladministration, namely an act of government officials against administrative law related to the procedures for making and issuing IPPKH can be held accountable for administrative law and given sanctions, in the form of light sanctions, moderate sanctions, severe sanctions and can be dismissed from their positions. Then, related to the IPPKH, it is considered that it is not in accordance with the applicable provisions or maladministration, then the granting of permits by the authorized official is invalid and can be cancelled, because it can harm the community and the IPPKH does not meet the legality that causes defects in government actions. Defects in authority cause government actions or government decisions to be null and void (nietig). If the IPPKH is procedurally flawed, it does not cause the government action or decision to be cancelled, but the existing deficiencies must be completed. If the deficiencies cannot be met, a cancellation can be requested, and not null and void. Keywords: maladministration; IPPKH; law enforcement; forest area